![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a,x4-4x3+8x2-16x+16
=(x4-4x3+4x2)+(4x2-16x+16)
=(x^2-2x)^2+(2x-4)^2
=x^2(x-2)^2+4(x-2)^2
=(x-2)^2(x^2+4)
![](https://rs.olm.vn/images/avt/0.png?1311)
1) Ta có: 2xy - x2 - y2 + 16
= -(x2 - 2xy + y2 - 16)
= -[(x - y)2 - 16]
= -(x - y - 4)(x - y + 4)
2) x3 + 2x2y + xy2 - 9x
= x(x2 + 2xy + y2 - 9)
= x[(x + y)2 - 9]
= x(x + y - 3)(x + y + 3)
3) x4 - 2x2 = x2(x2 - 2)
1. 2xy-x2-y2+16= -(x2-2xy+y2-16) = -(x2-2xy+y2)-16 = -(x-y)2-16= (x+y)2-42= (x+y-4).(x+y+4)
2. x3+2x2y+xy2-9x= (có sai đề không vậy?)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2-xy+x-y\)
\(=\left(x^2-xy\right)+\left(x-y\right)\)
\(=x\left(x-y\right)+\left(x-y\right)\)
\(=\left(x+1\right)\left(x-1\right)\)
b) \(2xy-x^2-y^2+16\)
\(=16-\left(x^2-2xy+y^2\right)\)
\(=4^2-\left(x-y\right)^2\)
\(=\left(4-x+y\right)\left(4+x-y\right)\)
c) \(x^2-6x-16\)
\(=x^2-6x+9-25\)
\(=\left(x^2-6x+9\right)-25\)
\(=\left(x-3\right)^2-5^2\)
\(=\left(x-3-5\right)\left(x-3+5\right)\)
\(=\left(x-8\right)\left(x+2\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
x6+3x4y2-8x3y3+3x2y4+y6= x6+3x4y2+3x2y4+y6-8x3y3=(x2+y2)3-(2xy)3
= (x2+y2-2xy)[(x2+y2)2+2xy(x2+y2)+(2xy)2]= (x-y)2(x4+6x2y2+y4+2x3y+2xy3)
(x2+y2-5)2-4x2y2-16xy-16=(x2+y2-5)2-(4x2y2+16xy+16)=(x2+y2-5)2-(2xy+4)2
=(x2+y2-5+2xy+4)(x2+y2-5-2xy-4)=(x2+2xy+y2-1)(x2-2xy+y2-9)=[(x+y)2-1][(x-y)2-32]=(x+y-1)(x+y+1)(x-y-3)(x-y+3)
x4+324=x4+36x2+324-36x2=(x2+18)2-(6x)2=(x2+18-6x)(x2+18+6x)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) x4 + x2 - 27x - 9
= (x4 - 27x) + x2 - 9
= x(x3 - 27) + (x - 3)(x + 3)
= x(x - 3)(x2 + 3x + 9) + (x - 3)(x + 3)
= (x - 3)(x3 + 3x2 + 9x + x + 3)
= (x - 3)(x3 + 3x2 + 10x + 3)
b) x2 - xy - x + y
= x(x - y) - (x - y)
= (x - 1)(x - y)
c) xy + 4 - x2 + 2y
= (xy + 2y) - (x2 - 4)
= y(x + 2) - (x - 2)(x + 2)
= (x + 2)(y - x + 2)
d) xy + y - 2(x + 1)
= y(x + 1) - 2(x + 1)
= (y - 2)(x + 1)
\(=\left[2\left(xy+4\right)-4\left(x+y\right)\right]\left[2\left(xy+4\right)+4\left(x+y\right)\right]=\left(2xy+8-4x-4y\right)\left(2xy+8+4y+4x\right)\\ =4\left(xy+4-2x-2y\right)\left(xy+4+2x+2y\right)\\ =4\left[x\left(y-2\right)-2\left(y-2\right)\right]\left[x\left(y+2\right)+2\left(y+2\right)\right]\\ =4\left(y-2\right)\left(y+2\right)\left(x-2\right)\left(x+2\right)\)